Crystal structure and characterization of the sulfamethazine–piperidine salt. Issue 3 (10th February 2023) - González-González, Juan Saulo; Pérez-Espinoza, Salvador; Martínez-Martínez, Francisco Javier; Pineda-Contreras, Armando; Canseco-Martínez, Miguel Ángel; Flores-Alamo, Marcos; García-Ortega, Héctor
Abstract : The piperidinium–sulfamethazinate salt was prepared by the solvent‐assisted grinding method. The ions are connected by N—H + …O and N—H + …N interactions. The self‐assembly of sulfamethazinate anions displays the amine–sulfa C (8) motif. The supramolecular architecture of the salt revealed the formation of interconnected supramolecular sheets. Abstract : Sulfamethazine [ N 1 ‐(4, 6‐dimethylpyrimidin‐2‐yl)sulfanilamide] is an antimicrobial drug that possesses functional groups capable of acting as hydrogen‐bond donors and acceptors, which make it a suitable supramolecular building block for the formation of cocrystals and salts. We report here the crystal structure and solid‐state characterization of the 1:1 salt piperidinium sulfamethazinate (PPD + ·SUL −, C5 H12 N + ·C12 H13 N4 O2 S − ) (I ). The salt was obtained by the solvent‐assisted grinding method and was characterized by IR spectroscopy, powder X‐ray diffraction, solid‐state 13 C NMR spectroscopy and thermal analysis [differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA)]. Salt I crystallized in the monoclinic space group P 21 / n and showed a 1:1 stoichiometry revealing proton transfer from SUL to PPD to form salt I . The PPD + and SUL − ions are connected by N—H + …O and N—H + …N interactions. The self‐assembly of SUL − anions displays the amine–sulfa C (8) motif. The supramolecular architecture of salt I revealed the formation of interconnected supramolecular sheets.